How Character-Centric Game Icon Design Affects the Perception of Gameplay - Xiaoxiao Cao (MDPI AG, 2021)
Mobile games are developing rapidly as an important part of the national economy. Gameplay is an important attribute, and a game’s icon sometimes determines the user’s initial impression. Whether the user can accurately perceive gameplay and affective quality through the icon is particularly critical. In this article, a two-stage perceptual matching procedure is used to evaluate the perceptual quality of six categories of games whose icons include characters as elements. First, 60 highly visual matching icons were selected as second-stage objects through classification tasks. Second, through the semantic differential method and correlation analysis, highly visual matching icons’ affective matching quality was measured. Finally, a series of icon samples were determined, and element analysis was carried out. Several methods were proposed for improving the perceptual quality of game icons. Studying the perceptual matching relationship can better enhance the interaction between designers, developers, and users.